Campus ministry leaders promoting student mental health at a large public university in the Southeast United States. Issue 1 (2nd January 2020) - Davidson, Charis; Turner-McGrievy, Gabrielle M.; Hilfinger Messias, DeAnne K.; Friedman, Daniela B.; Robillard, Alyssa G.; Schwiesow, Jessica; Warren, Peter
ABSTRACT: Despite the widespread, historic presence of campus ministries at public universities, there is limited research exploring campus ministers' role in student mental health. Prior research on campus ministries focused on student perspectives and organisational social norms. Conducted at a large public university in the Southeast, this research consisted of in-person semi-structured interviews with 12 campus ministry leaders about their experiences with students, including mental health challenges. The narrative interpretative analysis examined similarities and differences across campus ministers' experiences. Campus ministers reported providing pastoral care for students during crises, referring students to mental health providers and providing transportation to appointments. Major considerations informing referrals included mental health providers' attitudes towards religion, affordability of services, and their personal relationships with mental health providers. Although these campus ministry leaders reported actions to enhance access to student mental health services, additional training in mental health issues and institutional support would benefit both campus ministry leaders and their students.